Enhancing university students' engagement in studying assistive technology by case-based active learning: a pilot study in Hong Kong. - Li, Ke-Jing; Zhou, Yu-Jing; Wu, Hui-Dong; Luo, Chang-Liang; Liu, Wei; Hung, Percy; Wang, Kubert; Hu, Xiaoling; Wang, Yan; Li, Yan; Wen, Chunyi; Cheung, James Chung-Wai; et al. (Disability & Rehabilitation: Assistive Technology, 2025)
Assistive technology (AT) professionals are in pressing need with nowadays growing aged/disabled population, so as well-designed higher education programs in this field. This study designed and implemented a case-based active learning approach within an undergraduate course related to AT in Hong Kong, and assessed its impact on enhancing student engagement over two academic years. A total of twelve multimedia patient case dossiers on six major physical disabilities were created. Two cohorts of students enrolled in course "Rehabilitation Engineering and Assistive Technology" were instructed to utilize the case dossiers to facilitate their learning, understanding, and application of ATs for aged/disabled individuals. The Revised Two-Factor Study Process Questionnaire was employed to evaluate the student feedback on their learning experience, engagement, and learning approaches (i.e., Deep Approach, DA; and Surface Approach, SA) before and after the course. Upon completing the course, students' DA scores significantly increased from 29.4 ± 6.9 to 31.4 ± 8.9 (p = 0.013). Additionally, significantly moderate positive correlations were found between the DA-SA value and students' individual written report grades (p = 0.004) and overall grades (p = 0.048). In contrast, a significantly moderate negative correlation was identified between students' individual report grades and SA scores (p = 0.019). These findings support the feasibility and effectiveness of implementing case-based active learning in higher education within the field of AT, supporting future large-scale implementation and optimization of such case-based active learning and teaching strategy in the AT field. IMPLICATIONS FOR REHABILITATION: The assistive technology (AT) education is crucial for entry-level students or professionals in the interdisciplinary field of rehabilitation. Student-centered learning methods that promote lifelong AT learning warrant further investigation. The innovative AT-focused learning method implemented in a Hong Kong undergraduate course received positive responses and proved effective in enhancing students' engagement.